RNA pol II transcript abundance controls condensin accumulation at mitotically up‐regulated and heat‐shock‐inducible genes in fission yeast. (6th April 2015) - Nakazawa, Norihiko; Sajiki, Kenichi; Xu, Xingya; Villar‐Briones, Alejandro; Arakawa, Orie; Yanagida, Mitsuhiro
<x xml:space="preserve">Abstract</x> Condensin plays fundamental roles in chromosome dynamics. In this study, we determined the binding sites of condensin on fission yeast (Schizosaccharomyces pombe) chromosomes at the level of nucleotide sequences using chromatin immunoprecipitation (ChIP) and ChIP sequencing (ChIP‐seq). We found that condensin binds to RNA polymerase I‐, II‐ and III‐transcribed genes during both mitosis and interphase, and we focused on pol II constitutive and inducible genes. Accumulation sites for condensin are distinct from those of cohesin and DNA topoisomerase II. Using cell cycle stage and heat‐shock‐inducible genes, we show that pol II‐mediated transcripts cause condensin accumulation. First, condensin's enrichment on mitotically activated genes was abolished by deleting the sep1+ gene that encodes an M‐phase‐specific forkhead transcription factor. Second, by raising the temperature, condensin accumulation was rapidly induced at heat‐shock protein genes in interphase and even during mid‐mitosis. In interphase, condensin accumulates preferentially during the postreplicative phase. Pol II‐mediated transcription was neither repressed nor activated by condensin, as levels of transcripts per se did not change when mutant condensin failed to associate with chromosomal DNA. However, massive chromosome missegregation occurred, suggesting that abundant pol II transcription may require active condensin before proper chromosome segregation.